SYSTEM OF PRE-COURT RESOLVING TAX DISPUTES: GUARANTEE OF PROTECTION OF THE RIGHTS OF ENTREPRENEURS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article analyzes the legal and institutional framework for pre-trial resolution of tax disputes in the Republic of Uzbekistan, its role and effectiveness in protecting the rights of business entities. The study is based on the activities of the Expert Council on Tax Disputes under the Chamber of Commerce and Industry, introduced within the framework of reforms for 2023-2026, in particular, by the Presidential Decree adopted in July 2025.